A Practical Method of Policy Analysis by Estimating Effect Size - James L. Phelps (Educational Considerations, 2011)
The previous articles on class size and other productivity research paint a complex and confusing picture of the relationship between policy variables and student achievement. Missing is a conceptual scheme capable of combining the seemingly unrelated research and dissimilar estimates of effect size into a unified structure for policy analysis and decision making. This article builds a rationale for a unifying structure and consistent method of estimating effect size.
Keywords: class size; productivity; research; paradigm; outcomes; organization; Practical; method; policy; analysis; estimating